Complex word formation in contemporary syntactic frameworks: scientometric investigation and its relevance to grammar pedagogy - Nugraha, Danang Satria (JOALL (Journal of Applied Linguistics and Literature), 2025)
This study explored the evolving  research landscape on complex word formation within contemporary syntactic frameworks using a scientometric approach. Employing bibliographic data of 350 journal articles (2014 – 2024) retrieved from Scopus, the study examined publication trends, author productivity, and prominent publication avenues, utilizing VOSviewer for data visualization and network analysis. Findings revealed a growing body of literature, with an average of 34 publications annually and a notable increase in recent years. Verspoor and Culbertson emerged as the leading authors within this research focus, while Lingua and Languages were identified as the most prominent journal publishers. Keyword co-occurrence analysis revealed ten thematic clusters, highlighting the nature of this research domain. Two main clusters, “word constructions” (20.4%) and “syntax” (18.5%), dominated the landscape, followed by four intermediate clusters focusing on “compounds” (15.7%), “artificial intelligence” (14.85), “syntactic complexity” (10.2%), and “verb” (6.5%). Four minor clusters explored more specialized themes such as “speech perception and recursion” (4.6%), “syntactic processing and sentence comprehension” (3.7%), “syntax, semantics, and information structure” (3.7%), and “sign language and language evolution” (1.9%). These findings, to a certain extent, offer implications for grammar pedagogy, emphasizing the need for teaching approaches that reflect the interconnected nature of complex word formation.